2020
DOI: 10.1016/j.molmet.2020.101041
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inflammation in diabetes: From genetics to epigenomics evidence

Abstract: Background Diabetes is one of the greatest public health challenges worldwide, and we still lack complementary approaches to significantly enhance the efficacy of preventive and therapeutic approaches. Genetic and environmental factors are the culprits involved in diabetes risk. Evidence from the last decade has highlighted that deregulation in the immune and inflammatory responses increase susceptibility to type 1 and type 2 diabetes. Spatiotemporal patterns of gene expression involved in immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 115 publications
0
23
0
Order By: Relevance
“…While early GWASs showed that T2DM is associated with genetic variations in genes associated with insulin secretion and β-cell function (McCarthy et al 2010;Dimas et al 2014), later studies found that genes involved in peripheral insulin sensitivity and adipose tissue function such as PPARG and KLF14 are also associated with the incidence of T2DM (Voight et al 2010). Moreover, variations in genes regulating T-cell (e.g., PTPRJ and CMIP) or macrophage (e.g., MAEA) function or inflammatory signaling pathways (e.g., WWOX, MAP8IP1, IFNGR1, ST6GAL1, JAZF1, MAP3K1, MACROD1, NFE2L3, and TLR4) are also associated with the incidence of T2DM (Waeber et al 2000;Kooner et al 2011;Cho et al 2012;Manning et al 2012;Locke et al 2015;Shungin et al 2015;Flannick et al 2019;Liao et al 2019;Diedisheim et al 2020). While more inclusive GWAS and wholeexome sequencing studies are being updated (Mahajan et al 2018;Flannick et al 2019), many genetic variations associated with the incidence of T2DM are found in noncoding DNA regions.…”
Section: Association Between T2dm and Genetic Variations Associated Wmentioning
confidence: 99%
“…While early GWASs showed that T2DM is associated with genetic variations in genes associated with insulin secretion and β-cell function (McCarthy et al 2010;Dimas et al 2014), later studies found that genes involved in peripheral insulin sensitivity and adipose tissue function such as PPARG and KLF14 are also associated with the incidence of T2DM (Voight et al 2010). Moreover, variations in genes regulating T-cell (e.g., PTPRJ and CMIP) or macrophage (e.g., MAEA) function or inflammatory signaling pathways (e.g., WWOX, MAP8IP1, IFNGR1, ST6GAL1, JAZF1, MAP3K1, MACROD1, NFE2L3, and TLR4) are also associated with the incidence of T2DM (Waeber et al 2000;Kooner et al 2011;Cho et al 2012;Manning et al 2012;Locke et al 2015;Shungin et al 2015;Flannick et al 2019;Liao et al 2019;Diedisheim et al 2020). While more inclusive GWAS and wholeexome sequencing studies are being updated (Mahajan et al 2018;Flannick et al 2019), many genetic variations associated with the incidence of T2DM are found in noncoding DNA regions.…”
Section: Association Between T2dm and Genetic Variations Associated Wmentioning
confidence: 99%
“…However, glucose and lipid metabolism disorders caused by defects in insulin secretion and reduced responses to insulin-stimulated glycometabolism are the main pathological features of diabetes. Recent studies have found that metabolic disorder-induced glucotoxicity, oxidative stress, lipotoxicity, and endoplasmic reticulum stress can lead to systemic chronic inflammation that exacerbates the course of diabetes and diabetes-associated complications [ 2 , 3 ]. Increased activation of proinflammatory factors, such as IL-1β, has been reported to cause defective insulin secretion and insulin resistance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 Similarly, many genome-wide studies have confirmed that the genes associated with the development of type 2 diabetes are also oncogenes. 19 , 20 Although miR-140-5p was closely associated with tumors, it remained unclear whether miR-140-5p played an important role in insulin resistance and the development and progression of T2DM.…”
Section: Introductionmentioning
confidence: 99%